Base layer treating agent, preparation method thereof and composite waterproof system comprising base layer treating agent
By using carboxyl graft-modified epoxy resin as the base layer treatment agent, combined with components such as amine curing agents, to form a composite waterproof system, the adverse effects of asphalt-based waterproof coatings on the environment and human health and insufficient adhesion in the prior art are solved, and stronger waterproofing effect and excellent environmental protection performance are achieved.
Patent Information
- Application Number
- CN202411868211.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-12-18
AI Technical Summary
In the existing integrated roll coating composite waterproofing technology, asphalt-based non-curing waterproof coatings have an irritating odor, which is not good for the environment and human health, and lacks adhesion to polymer rolls, which poses a potential risk of water leakage.
Carboxy-grafted modified epoxy resin is used as the base layer treatment agent, and combined with amine-based curing agent, active diluent and accelerator to form a composite waterproof system to enhance the base surface sealing and adhesion of the waterproof material.
It improves the waterproof effect of the composite waterproof system, enhances the base surface sealing and adhesion of waterproof materials, reduces the risk of water leakage, and improves environmental protection performance.
Smart Images

Figure BDA0005195045660000151 
Figure BDA0005195045660000161 
Figure BDA0005195045660000191
Abstract
Description
Technical Field
[0001] The invention relates to the field of building waterproofing, and in particular to a base treatment agent and a preparation method thereof, and a composite waterproofing system containing the same. Background Art
[0002] In recent years, in order to deal with the problem of building leakage, the "roll-coated integrated composite waterproofing technology" has been developed to fundamentally solve the defects of traditional waterproofing construction. The key core of this technology is to use asphalt-based non-curing waterproof coating to paste modified asphalt waterproofing membrane to form a composite waterproof layer, thereby achieving a good waterproof effect.
[0003] The above-mentioned technology uses ordinary asphalt-based non-curing waterproof coatings, which have a pungent odor, have adverse effects on the environment and human health, and have insufficient adhesion to polymer coils. Therefore, there is still a need to improve the existing coil-coated integrated composite waterproof system. Summary of the invention
[0004] In view of this, the present invention proposes a base treatment agent and a preparation method thereof, and a composite waterproof system containing the same, which can increase the sealing performance of the base surface and enhance the adhesion between the waterproof coating and the waterproof membrane and the base surface, thereby making the waterproof effect of the composite waterproof system stronger and improving the environmental friendliness of the composite waterproof system.
[0005] The present invention provides the following technical solutions:
[0006] A base treatment agent for a composite waterproof system comprises a carboxyl grafted epoxy resin, an amine curing agent, a reactive diluent, and an accelerator; wherein the epoxy value of the carboxyl grafted epoxy resin is 0.30-0.38 eq / 100 g, as determined by a hydrochloric acid-acetone method; the content of the amine curing agent is determined according to the epoxy value of the carboxyl grafted epoxy resin, the number of active hydrogen atoms on the amine group in the amine curing agent molecule, and the molecular weight of the amine curing agent; and the molar ratio of the amine curing agent, the reactive diluent, and the accelerator is 1:(4-5):(0.2-0.4).
[0007] Optionally, the carboxyl graft-modified epoxy resin is prepared from a composition comprising a bisphenol A type epoxy resin, a carboxyl functional monomer and a thermal initiator.
[0008] Optionally, the molar ratio of the bisphenol A epoxy resin, the carboxyl functional monomer, and the thermal initiator is 1:(2.2-2.4):(0.1-0.3).
[0009] Optionally, the carboxyl functional monomer includes one or more of the following substituted or unsubstituted carboxylic acids: C16-C20 carbenoid carboxylic acid, acrylic acid, maleic anhydride; and / or, the thermal initiator is an azo initiator or an organic peroxide.
[0010] Optionally, the content of the amine curing agent is calculated according to the following formula:
[0011] W=(M / H n )×E×1.15
[0012] Where:
[0013] W is the mass of amine curing agent required for every 100g of carboxyl graft-modified epoxy resin;
[0014] M—molecular weight of amine curing agent;
[0015] H n —The number of active hydrogen atoms on the amine group in the amine curing agent molecule; and
[0016] E—Epoxy value of carboxyl grafted modified epoxy resin.
[0017] Optionally, the amine curing agent includes one or more of aliphatic amines, alicyclic amines, aromatic amines, and polyamides; the reactive diluent is an epoxy or hydroxyl solvent; and the accelerator is a phenolic accelerator.
[0018] Optionally, the accelerator includes one or more of phenol, 2,4,6-tris(dimethylaminomethyl)phenol, resorcinol, aminophenol, and halogenated phenol.
[0019] The present invention also provides a method for preparing the above-mentioned base treatment agent, comprising the following steps: mixing an amine curing agent, a reactive diluent, and an accelerator to obtain a mixture; and mixing a carboxyl graft-modified epoxy resin with the mixture to obtain the base treatment agent.
[0020] The present invention also provides a composite waterproof system, which includes a base treatment layer, a non-asphalt non-cured waterproof coating layer, and an environmentally friendly waterproof coiled material stacked in sequence; wherein the base treatment layer is coated with the base treatment agent as described above.
[0021] Optionally, the environmentally friendly waterproof membrane is a non-asphalt self-adhesive waterproof membrane or a polymer waterproof membrane.
[0022] According to the technical solution of the present invention, the base treatment agent of the present invention includes a carboxyl grafted modified epoxy resin, and is used in combination with other components to increase the sealing of the base surface (such as a concrete surface), improve the moisture resistance of the base surface, reduce the risk of bulging of the waterproof layer caused by water vapor penetration, and enhance the adhesion between the waterproof coating and the waterproof roll and the base surface, so that the waterproof effect of the composite waterproof system is stronger. The preparation method of the base treatment agent of the present invention is simple and convenient for industrial production. The composite waterproof system of the present invention is a non-asphalt-based composite waterproof system, which is sequentially arranged on the base surface treated with the base treatment agent of the present invention. The composite waterproof system has excellent creep and elongation, can adapt to the deformation of the base surface, and can automatically heal cracks below 2mm; and can adapt to low temperature (-15°C) and high temperature (50°C) construction environments, and still achieve a first-class waterproof effect; and there is no obvious smoke during the construction process, which has excellent environmental protection. DETAILED DESCRIPTION
[0023] For ease of understanding of the present invention, the present invention will be described more fully below with reference to examples. Preferred embodiments of the present invention are provided in the examples. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0024] In the existing "roll-coated integrated composite waterproofing technology", the traditional asphalt-based non-curing waterproof coating used is mainly composed of rubber and asphalt. Among them, the rubber component reduces the high and low temperature performance and ductility of the asphalt-based non-curing waterproof coating itself, and even loses the waterproof effect; secondly, asphalt has defects such as low equivalent softening point and poor low temperature resistance, and asphalt is easy to volatilize irritating odor at high temperature, which seriously pollutes the environment and harms the health of construction workers. In addition, when the asphalt-based non-curing waterproof coating is used in combination with polymer waterproofing coils, the asphalt contains some free oil molecules, which will penetrate into the polymer, destroy the original structure of the polymer, and cause the performance of the polymer waterproofing coil to decay. During the long-term use of this composite waterproofing system of asphalt-based non-curing waterproof coating and polymer coils, there is a repulsive force between the interfaces of the two, making it difficult to form a skin-like full-stick construction effect, and there is a hidden danger of water leakage. In the existing roll-coated composite construction process, there are many pores on the base, and there is water vapor in the construction base, and bulging will occur during the construction process, thus posing a risk of water leakage. The base treatment agent of the present invention can fill the gaps in the construction base surface, increase the sealing of the base, improve the moisture resistance of the base surface, inhibit the risk of bulging of the waterproof layer due to water vapor penetration, and enhance the adhesion between the waterproof material and the base, so that the waterproof effect is stronger. The composite waterproof system of the present invention is a non-asphalt-based waterproof system, which is sequentially arranged on the base surface treated with the base treatment agent of the present invention. The non-asphalt-based non-curing waterproof coating composite environmentally friendly waterproof roll material, wherein the construction convenience of the non-asphalt-based non-curing waterproof coating is comparable to that of the traditional asphalt-based non-curing waterproof coating, and the material has excellent creep and elongation, can adapt to the deformation of the base, can automatically heal cracks below 2 mm, and there is no obvious smoke during the construction process. This new non-asphalt composite waterproof system is a huge breakthrough in the traditional roll-coated integrated composite waterproof technology, and is better suitable for areas with higher environmental protection requirements.
[0025] In an embodiment of the present invention, the base treatment agent for the composite waterproof system of the present invention comprises a carboxyl graft-modified epoxy resin, an amine curing agent, a reactive diluent, and an accelerator.
[0026] The carboxyl grafted modified epoxy resin is prepared from a composition comprising a bisphenol A epoxy resin, a carboxyl functional monomer and a thermal initiator. The molar ratio of the bisphenol A epoxy resin, the carboxyl functional monomer and the thermal initiator is 1:(2.2-2.4):(0.1-0.3), for example 1:(2.2-2.4):0.2.
[0027] The bisphenol A epoxy resin can be commercially available or prepared by a method known to those skilled in the art, for example, by condensing bisphenol A and epichlorohydrin under alkaline conditions, washing with water, and refining by desolventizing. The bisphenol A epoxy resin is usually bisphenol A epoxy resin E-51, bisphenol A epoxy resin E-44, or bisphenol A epoxy resin E-42; its epoxy value is 0.38-0.54 eq / 100 g, as determined by the hydrochloric acid-acetone method.
[0028] The carboxyl functional monomer may include one or more of the following substituted or unsubstituted carboxylic acids: C16-C20 carboene carboxylic acids, acrylic acid, maleic anhydride and its derivatives; for example, oleic acid ((Z)-9-octadecenoic acid, CAS No. 112-80-1), palmitoleic acid, cis-eicos-9-enoic acid, or maleic anhydride.
[0029] The thermal initiator may be an azo initiator or an organic peroxide, for example, one or more of the following: azobisisobutyronitrile (AIBN), dibenzoyl peroxide (BPO).
[0030] The preparation method of carboxyl graft-modified epoxy resin comprises:
[0031] (1) adding bisphenol A epoxy resin and carboxyl functional monomer in a molar ratio of 1:(2.2-2.4) into a reaction vessel equipped with a stirring device, and uniformly stirring at a temperature of 90-120° C., such as 110° C., at a stirring rate of 400-800 r / min for 5-10 min;
[0032] (2) Add the thermal initiator to the bisphenol A type epoxy resin in a molar ratio of (0.1-0.3):1 into the reaction vessel, stir evenly at a temperature of 90-120°C, such as 110°C, at a stirring rate of 400-800 r / min for 5-10 min, and then continue stirring for 4-5 h under the reaction condition of a temperature of 110-120°C to obtain a carboxyl grafted modified epoxy resin.
[0033] The epoxy value of the carboxyl graft-modified epoxy resin is 0.30-0.38 eq / 100 g, for example 0.32-0.35 eq / 100 g, as measured by a hydrochloric acid-acetone method.
[0034] The amine curing agent may include one or more of aliphatic amines, alicyclic amines, aromatic amines and polyamides, for example, may include one or more of ethylenediamine EDA, diethylenetriamine DETA and triethylenetetramine TETA.
[0035] The content of the amine curing agent is determined according to the epoxy value of the carboxyl grafted epoxy resin, the number of active hydrogen atoms on the amine group in the amine curing agent molecule, and the molecular weight of the amine curing agent; for example, the content of the amine curing agent is calculated according to the following formula:
[0036] W=(M / H n )×E×1.15
[0037] Where: W is the mass of amine curing agent required for every 100g of carboxyl grafted epoxy resin; M is the molecular weight of amine curing agent; H is n —The number of active hydrogen atoms on the amine group in the amine curing agent molecule; E—The epoxy value of the carboxyl grafted modified epoxy resin.
[0038] The reactive diluent can promote the curing reaction, and is usually an epoxy or hydroxy solvent, such as allyl glycidyl ether AGE, n-butyl glycidyl ether BGE, benzyl alcohol, and epichlorohydrin.
[0039] The accelerator can accelerate the curing reaction and improve the construction efficiency; it is usually a phenolic accelerator, for example, it may include one or more of phenol, 2,4,6-tris(dimethylaminomethyl)phenol, resorcinol, aminophenol, halogenated phenols such as (o-chlorophenol, p-chlorophenol, 2,5-dichlorophenol and 2,4,5-trichlorophenol, etc.).
[0040] In an embodiment of the present invention, the method for preparing a base treatment agent includes: providing a carboxyl grafted modified epoxy resin; mixing an amine curing agent, an active diluent, and an accelerator to obtain a mixture; mixing the carboxyl grafted modified epoxy resin and the mixture to obtain a base treatment agent.
[0041] In the step of mixing the amine curing agent, the reactive diluent and the accelerator, the amount of the amine curing agent is determined according to the amount of the carboxyl-grafted modified epoxy resin, and the amine curing agent, the reactive diluent and the accelerator are mixed at a molar ratio of 1:(4-5):(0.2-0.4), for example, usually stirred at room temperature for 20-30 minutes.
[0042] In the step of mixing the carboxyl graft modified epoxy resin and the mixture, the carboxyl graft modified epoxy resin and the mixture are usually mixed at a stirring rate of 400-600 r / min for 5-7 minutes.
[0043] In an embodiment of the present invention, the non-asphalt-based composite waterproof system of the present invention comprises a base treatment layer, a non-asphalt non-cured waterproof coating layer, and an environmentally friendly waterproof membrane stacked in sequence; wherein the base treatment layer is obtained from the above-mentioned base treatment agent.
[0044] In an embodiment of the present invention, the non-asphalt non-curing waterproof coating may include 35-65% softening oil, 3.5-10% wax powder, 15-25% thermoplastic elastomer, 15-25% resin, 1-3% coupling agent, 1-5% antioxidant, 3-6% dispersant, 2-6% pigment and 5-20% filler, based on the total weight of the non-asphalt non-curing waterproof coating; the sum of the weight percentages of each component in the non-asphalt non-curing waterproof coating is 100%, based on the total weight of the non-asphalt non-curing waterproof coating.
[0045] Softening oil is one or more of low-volatility naphthenic oil, reduced oil, paraffin oil, white wax oil, and aromatic oil, of which the volatile matter should be ≤8g / Kg. The volatile matter is determined according to Section 8.2 of GB / T 34682-2017. It is mainly used as a good solvent for the modifier to reduce the viscosity of the system and improve the low-temperature performance. The flash point of softening oil is 230-300℃, which is determined by the closed cup flash point determination method.
[0046] Wax powder is polyethylene wax or polypropylene wax, which can improve the storage stability of the product, reduce the viscosity of the product, and improve the high temperature performance. The softening point of wax powder is 105-130℃, which is determined according to the asphalt softening point determination method.
[0047] Thermoplastic elastomers may include one or more of hydrogenated styrene-butadiene-styrene block copolymer (SEBS), hydrogenated styrene-isoprene-styrene block copolymer (SEPS), and styrene-butadiene rubber (SBR), wherein the main function of hydrogenation is to break the unstable double bond structure on the chain forging of the original copolymer elastomer, reduce the content of its own active hydrogen, thereby improving its anti-aging property, so that the modifier can still maintain a good modification effect during the later aging process, and provide the product with certain strength and elongation. Among them, SEBS and SEPS require the Shore A hardness range to be between 40-80, measured using a Shore durometer, and the melt index at 200°C is less than 1g / 10min, tested by a melt index tester; SBR requires the raw rubber Mooney viscosity to be 50-70ML100°C1+4, measured using a Mooney viscometer.
[0048] The resin may include one or more of cold-polymerized C5 hydrogenated petroleum resin, cold-polymerized C9 hydrogenated petroleum resin, alicyclic resin (DCPD), C5 / C9 copolymer resin, which has good miscibility, low melting point and excellent water resistance, and can improve the bonding effect of the system. The hydrogenation treatment also improves the aging resistance of the resin itself. The softening point of the resin is 100-130°C, measured by the ring and ball method.
[0049] The coupling agent may be a silane coupling agent, generally including one or more of n-octyltriethoxysilane, n-hexyltriethoxysilane, n-decyltrimethoxysilane, etc. The coupling agent mainly reduces the surface energy of the filler, improves the compatibility of the filler with the system, avoids the agglomeration of the fillers, and promotes the dispersion of the fillers.
[0050] The pigment may include one or more of iron oxide red, iron oxide yellow, iron oxide brown, chromium oxide green, chrome yellow, and iron blue. The function of the dispersant is to promote the dispersion of the pigment and ensure uniform color. The dispersant may be an oily dispersant, which may be selected from one or more of KYC-913 and KYC-919 purchased from Keying Chemical. The antioxidant may be a hindered phenol antioxidant, such as pentaerythritol tetra[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate (antioxidant 1010).
[0051] Fillers include one or more of stone powder, quartz powder, talcum powder, and heavy calcium. Fillers can comprehensively improve the performance and storage stability of the coating, and fillers can also reduce the production cost of the coating.
[0052] In an embodiment of the present invention, the non-bituminous non-curing waterproof coating is commercially available or can be prepared by methods known to those skilled in the art, for example:
[0053] (1) Add softened oil into the reactor and heat to 150-160°C under stirring;
[0054] (2) adding antioxidant, thermoplastic elastomer and resin, stirring and heating to 170-175°C;
[0055] (3) After the particles are completely dispersed and no obvious agglomeration is observed, add the dispersant and stir at 172-176°C for 2-2.5 hours;
[0056] (4) Add filler and mix for 0.2-0.4h; then add coupling agent and stir at 170-175°C for 1-1.5h to ensure uniform dispersion;
[0057] (5) Stop heating, add wax powder and pigment, and continue stirring for 1-1.5 hours;
[0058] (6) When the temperature drops to 120-130℃, put the product into an iron barrel and seal it for storage.
[0059] The environmentally friendly waterproof membrane can be a non-asphalt self-adhesive waterproof membrane or a polymer waterproof membrane.
[0060] The non-asphalt self-adhesive waterproof membrane may be any non-asphalt self-adhesive waterproof membrane commonly used in the art, for example, it may include 30-55% softening oil, 15-25% thermoplastic elastomer, 15-25% tackifying resin, 1-3% coupling agent, 1-5% antioxidant, 1-5% cross-linking agent, 10-20% filler, based on the total weight of the non-asphalt self-adhesive waterproof membrane.
[0061] The softening oil may be a low flash point thinning oil or an aromatic oil, which is mainly used as a good solvent for the modifier to reduce viscosity and improve low temperature performance. The thermoplastic elastomer may include one or more of styrene / butadiene / styrene block copolymer (SBS), SBR, and styrene-isoprene-styrene block copolymer (SIS). The tackifying resin may include one or more of rosin resin, coumarone resin, and terpene resin, which are mainly used to improve the initial adhesion of the waterproof membrane. The coupling agent is a silane coupling agent, which generally includes one or more of γ-aminopropyl triethoxysilane, n-octyl triethoxysilane, n-hexyl triethoxysilane, and vinyl tri(β-methoxyethoxy) silane. The antioxidant may be an antioxidant commonly used in the art, such as tetra[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol ester (antioxidant 1010). The cross-linking agent is a sulfur- or nitrogen-containing cross-linking agent, which may generally include one or more of sulfur, a vulcanization accelerator (TMTD), and N-oxydiphenyl-N'-isopropyl-p-aniline (MOR). The cross-linking agent can increase the degree of cross-linking of the polymer in the waterproofing membrane and improve the anti-aging property. The filler is a filler with a high specific surface area, which is generally calcium hydroxide, vermiculite, kaolin, etc., which can reduce the density of the product and expand the application construction area. The non-asphalt self-adhesive waterproofing membrane has an isolation film on both the upper and lower sides, which can be a PET isolation film.
[0062] Non-bituminous self-adhesive waterproof membranes are commercially available or can be prepared by methods known to those skilled in the art, for example comprising the following steps:
[0063] (1) Add softened oil into the reactor and heat to 160-165°C under stirring;
[0064] (2) adding antioxidant, thermoplastic elastomer and tackifying resin in sequence, stirring and heating to 170-175° C.;
[0065] (3) After the mixture is completely dispersed and there is no obvious agglomeration of particles, add the crosslinking agent, stir at 172-176°C for 2-2.5 hours, then add the coupling agent and continue stirring for 30 minutes;
[0066] (4) Add filler and stir at 170-175°C for 1-1.5 hours to ensure uniform dispersion;
[0067] (5) The non-asphalt self-adhesive waterproof membrane can be obtained by cooling and molding using a PET isolation film.
[0068] The polymer waterproofing membrane can be any polymer waterproofing membrane commonly used in the art, for example, it can include 60-70% ethylene propylene copolymer, 15-25% metallocene polyethylene, 8-15% linear low density polyethylene (LLDPE), 5-10% ethylene octene polymer (POE), 1-3% antioxidant 1010, and 2-5% masterbatch, based on the total weight of the polymer waterproofing membrane. The number average molecular weight of the ethylene propylene copolymer is 10000-30000 g / mol, measured according to the gel permeation chromatography (GPC) method, and is usually EPDM 1230 purchased from DuPont of the United States. The metallocene polyethylene is usually 5815 purchased from Dow Chemical Company. The linear low density polyethylene (LLDPE) is usually 7042 purchased from Guangzhou Petrochemical Company. The ethylene octene polymer (POE) is usually 8150 purchased from Dow Chemical Company. The masterbatch is usually 1010 purchased from Dongguan Meize Plastic Pigment Co., Ltd.
[0069] The polymer waterproofing membrane is commercially available or can be prepared by methods known to those skilled in the art. For example, 60-70% of ethylene propylene copolymer, 15-25% of metallocene polyethylene, 8-15% of linear low density polyethylene (LLDPE), 5-10% of ethylene octene polymer (POE), 1-3% of antioxidant 1010, and 2-5% of masterbatch can be added to a mixer, stirred and mixed at a stirring rate of 15-30 r / min for 30-60 minutes, and then calendered and formed to obtain the polymer waterproofing membrane.
[0070] In an embodiment of the present invention, the preparation method of the non-asphalt-based composite waterproofing system of the present invention comprises:
[0071] (1) Ensure that there is no visible water on the base surface and remove dust from the base surface;
[0072] (2) applying the base treatment agent of the present invention to a thickness of 0.3-0.6 mm to obtain a base treatment layer;
[0073] (3) applying a non-asphalt non-curing waterproof coating heated to a state that it can be easily stirred to a side of the base treatment layer away from the base surface by scraping, wherein the non-asphalt non-curing waterproof coating has a scraping thickness of 1.5-2.0 mm, to obtain a non-asphalt non-curing waterproof coating layer;
[0074] (4) Before the non-asphalt non-curing waterproof coating is completely cooled, the environmentally friendly waterproof membrane is laid on the side of the non-asphalt non-curing waterproof coating layer away from the base treatment layer to obtain the non-asphalt-based composite waterproof system.
[0075] The composite waterproof system achieves good waterproofing effect, has a wider construction temperature range, and has excellent environmental performance. It can be widely used in buildings, high-speed railways, subways, tunnels or other engineering fields.
[0076] The present invention is described below by specific examples. The examples described below are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention. If no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in the art or the product instructions are used, or the methods are carried out at normal temperature and pressure. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be obtained commercially.
[0077] Example 1
[0078] The non-asphalt composite waterproofing system includes a base treatment agent layer, a non-asphalt non-curing waterproof coating, and a non-asphalt self-adhesive waterproofing membrane.
[0079] (I) Epoxy layer treatment agent
[0080] (A) Preparation of carboxyl graft-modified epoxy resin:
[0081] (1) bisphenol A epoxy resin E51 (368 g, model CYD-128, purchased from Baling Petrochemical) and oleic acid (621.41 g, CAS No. 112-80-1, purchased from Shandong Chuangli New Materials Co., Ltd.) were added into a reactor equipped with a stirring device at a molar ratio of 1:2.2, and stirred uniformly at a temperature of 110° C. and a stirring rate of 600 r / min for 8 min;
[0082] (2) AIBN (32.84 g) was added into the reactor at a molar ratio of 0.2:1 with E51, and the mixture was stirred at 110° C. at a stirring rate of 600 r / min for 7 min, and then stirred at 120° C. for 5 h to obtain 335.85 g of modified epoxy resin 1.
[0083] The epoxy value of carboxyl grafted epoxy resin 1 is 0.35 eq / 100 g. Its structure is characterized by infrared spectroscopy, 1739.02 cm -1 An obvious characteristic absorption peak of anhydride appeared at the oleic acid residue, indicating that oleic acid had been grafted onto the epoxy resin molecular chain.
[0084] (B) Based on the epoxy value and weight of the above-mentioned carboxyl graft-modified epoxy resin 1, according to the following formula
[0085] W=(M / H n )×E×1.15
[0086] The mass of ethylenediamine EDA required for every 100g of carboxyl-grafted modified epoxy resin is calculated to be 6.04g (0.1mol), so the total mass of ethylenediamine EDA required for the above carboxyl-grafted modified epoxy resin 1 is 20.29g (0.34mol).
[0087] 147.08 g (1.36 mol) of benzyl alcohol and 18.05 g (0.068 mol) of 2,4,6-tris(dimethylaminomethyl)phenol were weighed at a molar ratio of ethylenediamine EDA: benzyl alcohol: 2,4,6-tris(dimethylaminomethyl)phenol of 1:4:0.2. Ethylenediamine EDA, benzyl alcohol and 2,4,6-tris(dimethylaminomethyl)phenol were stirred and mixed at room temperature at a rate of 500 r / min for 25 min to obtain a mixture;
[0088] (C) The carboxyl graft-modified epoxy resin obtained in (A) and the mixture obtained in (B) were mixed at a stirring rate of 500 r / min for 6 minutes to obtain a base treatment agent.
[0089] The preparation and composition of the base treatment layer are summarized in Table 1.
[0090] (II) Non-asphalt non-curing waterproof coating
[0091] It includes the following parts by weight: 50 parts of aromatic oil (model AL-09, purchased from Guangzhou Dagang Petroleum Technology Co., Ltd.), 5 parts of polyethylene wax (model PEW-0360, purchased from Nanjing Tianshi New Materials Technology Co., Ltd.), 20 parts of thermoplastic elastomer (SEBS:SBR=4:6) (models are YH502 and SBR1502, purchased from China Petrochemical Group Baling Petrochemical Company), 25 parts of C5 hydrogenated petroleum resin (model H5-1000, purchased from Henghe Materials Technology Co., Ltd.), 2 parts of KH-550, 10102 parts of antioxidant, 135 parts of dispersant KYC-9, 3 parts of iron oxide red (model H130, purchased from Henan Huamei Chengde Pigment Co., Ltd.), and 15 parts of filler talc.
[0092] (1) Add aromatic oil into a reactor and heat to 155° C. under stirring at a stirring rate of 300 r / min;
[0093] (2) adding antioxidant 1010, thermoplastic elastomer and C5 hydrogenated petroleum resin, and heating to 170° C. at a stirring rate of 500 r / min;
[0094] (3) After the particles are completely dispersed and no obvious agglomeration is observed, add dispersant KYC-913 and stir at 172 °C for 2 h;
[0095] (4) Add talcum powder as filler and mix for 0.2-0.4h; then add coupling agent KH-550 and stir at 170°C for 1h to ensure uniform dispersion;
[0096] (5) Stop heating, add polyethylene wax powder and pigment red iron oxide, and continue stirring for 1 hour;
[0097] (6) When the temperature is naturally cooled to 120°C, the obtained waterproof coating is placed in an iron barrel and sealed for storage for future use.
[0098] (III) The non-asphalt self-adhesive waterproof membrane comprises the following parts by weight: 45 parts of cyclohexane oil, 15 parts of SBS, 15 parts of coumarone resin, 2 parts of KH-550, 10102 parts of antioxidant, 1 part of sulfur, and 20 parts of vermiculite.
[0099] (1) Add cyclohexane oil into a reactor and heat to 160° C. under stirring at a stirring rate of 300 r / min;
[0100] (2) adding antioxidant 1010, SBS, and coumarone resin in sequence, stirring at a stirring rate of 500 r / min and heating to 170°C;
[0101] (3) After the mixture is completely dispersed and there is no obvious agglomeration of particles, add the crosslinking agent sulfur, keep the mixture at 172°C and stir at a stirring rate of 500 r / min for 2 h, then add the coupling agent KH-550 and continue stirring for 30 min;
[0102] (4) Adding vermiculite filler, stirring at 170°C and 600 r / min for 1 h to ensure uniform dispersion;
[0103] (5) The non-asphalt self-adhesive waterproof membrane can be obtained by cooling and molding using a PET isolation film.
[0104] (IV) Preparation of non-asphalt composite waterproofing system
[0105] (1) Remove dust from the base surface and ensure that there is no visible water on the base surface;
[0106] (2) coating the base treatment agent prepared in step (A) with a coating thickness of 0.5 mm to obtain a base treatment layer;
[0107] (3) applying a non-asphalt non-curing waterproof coating heated to a state that it can be easily stirred to a side of the base treatment layer away from the base surface by scraping, wherein the non-asphalt non-curing waterproof coating has a scraping thickness of 1.5 mm, to obtain a non-asphalt non-curing waterproof coating layer;
[0108] (4) After the non-asphalt non-curing waterproof coating is applied, the non-asphalt self-adhesive waterproof membrane is immediately laid on the side of the non-asphalt non-curing waterproof coating layer away from the base treatment layer to obtain the non-asphalt-based composite waterproof system.
[0109] Embodiment 2-20
[0110] The steps of Example 1 were repeated, except that the preparation conditions, material composition and dosage of (I) the base treatment layer were changed; see Table 1 for details.
[0111] Table 1 Preparation and composition of the base treatment agent of Examples 1-20
[0112]
[0113]
[0114] *The molar ratio of the three is the molar ratio of amine curing agent, reactive diluent and accelerator
[0115] Embodiment 21
[0116] The steps of Example 1 were repeated, except that the composition of the thermoplastic elastomer in the preparation of (II) the non-asphalt non-curing waterproof coating was SEBS:SBR=5:5.
[0117] Embodiment 22
[0118] The steps of Example 1 were repeated, except that the composition of the thermoplastic elastomer in the preparation of (II) the non-asphalt non-curing waterproof coating was SEBS:SEPS=6:4.
[0119] Embodiment 23
[0120] The steps of Example 1 were repeated, except that the composition of the thermoplastic elastomer in the preparation of (II) the non-asphalt non-curing waterproof coating was SBR:SEPS=7:3.
[0121] Embodiment 24
[0122] The steps of Example 1 were repeated, except that the non-asphalt self-adhesive waterproof membrane in (III) was replaced by a polymer waterproof membrane, which included the following parts by weight: 60 parts of ethylene propylene copolymer, 15 parts of metallocene polyethylene, 15 parts of linear low-density polyethylene (LLDPE), 7 parts of ethylene octene polymer (POE), 10101 parts of antioxidant, and 2 parts of masterbatch.
[0123] Comparative Example 1
[0124] The steps of Example 1 were repeated, except that the non-asphalt non-curing waterproof coating was replaced with an asphalt-based non-curing waterproof coating in (II), and the asphalt-based non-curing waterproof coating contained: 50 parts of 200# asphalt, 10 parts of 90# asphalt, 5 parts of SBS, 3 parts of SIS, 5 parts of SBR, 4 parts of polyethylene wax, 2 parts of coupling agent KH-550, and 21 parts of vermiculite filler.
[0125] Comparative Example 2
[0126] The steps of Comparative Example 1 were repeated, except that the non-asphalt self-adhesive waterproof membrane in (III) was replaced by the polymer waterproof membrane in Example 24.
[0127] Comparative Example 3
[0128] The steps of Example 1 were repeated, except that step (I) was not performed and step (IV)(2) was omitted, and the non-asphalt non-curing waterproof coating was directly applied to the base surface.
[0129] Comparative Example 4
[0130] The steps of Example 1 were repeated, except that step (A) was not performed in step (I), that is, bisphenol A type epoxy resin E51 was directly used to replace the carboxyl graft-modified epoxy resin 1 in (B) to prepare the base treatment agent.
[0131] Performance Testing
[0132] The performance of the non-asphalt-based composite waterproofing system prepared in the above-mentioned embodiments and comparative examples was tested. The present invention was tested according to actual application scenarios, and those not explicitly specified were tested under a standard environment of room temperature of 23°C.
[0133] Peel strength: The bonding area of the non-asphalt-based composite waterproofing system prepared in the above-mentioned embodiments and comparative examples is 50 mm×75 mm on the cement-based surface. After bonding, a 1 kg weight is used to pressurize the center for 10 minutes. Then, it is placed under standard conditions of temperature (23±2)°C and relative humidity (30-70)% for 24 hours. According to the GB / T 328.20-2007 standard test, it should be placed at the test required temperature for 1 hour before testing.
[0134] Shear force: The bonding area of the non-asphalt-based composite waterproofing system prepared in the above-mentioned embodiments and comparative examples is 50 mm×50 mm on the cement-based surface. After bonding, a 1 kg weight is used to pressurize the center for 10 minutes. Then, it is placed under standard conditions of temperature (23±2)°C and relative humidity (30-70)% for 24 hours. Test according to GB / T 328.23-2007 standard. The sample length should ensure that the initial distance between the clamps is (200±5) mm. The test is carried out at (23±2)°C and the tensile speed is (100±10) mm / min.
[0135] Water penetration resistance: Tested according to Section 7.17.1 of JC / T 2428-2017. Specifically, a hole with a diameter of about 10 mm was opened in the middle of the specimen until it reached the cement base surface. The specimen was placed in a mortar impermeability tester, with the coating surface facing the water, and pressurized to 1.0 MPa for 24 hours. After the test, the non-asphalt-based composite waterproofing system was shoveled off to observe whether there was visible water on the bonding surface. No visible water means no water penetration.
[0136] The test results of the composite waterproof system of each embodiment and comparative example are summarized in Table 2.
[0137] Table 2 Performance of the composite waterproof system of each embodiment and comparative example
[0138]
[0139]
[0140] The non-asphalt composite waterproofing system prepared by the present invention also has a full-adhesion construction effect under high and low temperature environments, broadens the application scope of conventional roll-coated composite waterproofing construction, achieves a good waterproofing effect, and has excellent environmental protection performance.
[0141] The above specific implementations do not constitute a limitation on the protection scope of the present invention. It should be understood by those skilled in the art that various modifications, combinations, sub-combinations and substitutions may occur depending on design requirements and other factors. Any modification, equivalent substitution and improvement made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A base treatment agent for a composite waterproof system, characterized in that: It includes carboxyl grafted modified epoxy resin, amine curing agent, active diluent, and accelerator; Wherein, the epoxy value of the carboxyl graft-modified epoxy resin is 0.30-0.38 eq / 100 g, as determined by the hydrochloric acid-acetone method; The content of the amine curing agent is determined according to the epoxy value of the carboxyl grafted modified epoxy resin, the number of active hydrogen atoms on the amine group in the amine curing agent molecule, and the molecular weight of the amine curing agent; Furthermore, the molar ratio of the amine curing agent, the reactive diluent and the accelerator is 1:(4-5):(0.2-0.4).
2. The base treatment agent according to claim 1, characterized in that: The carboxyl graft-modified epoxy resin is prepared from a composition comprising a bisphenol A epoxy resin, a carboxyl functional monomer and a thermal initiator.
3. The base treatment agent according to claim 2, characterized in that: The molar ratio of the bisphenol A epoxy resin, the carboxyl functional monomer and the thermal initiator is 1:(2.2-2.4):(0.1-0.3).
4. The base treatment agent according to claim 2, characterized in that: The carboxyl functional monomer includes one or more of the following substituted or unsubstituted carboxylic acids: C16-C20 carbenyl carboxylic acid, acrylic acid, maleic anhydride; and / or, The thermal initiator is an azo initiator or an organic peroxide.
5. The base treatment agent according to any one of claims 1 to 4, characterized in that: The content of the amine curing agent is calculated according to the following formula: W=(M / H n )×E×1.15 Where: W is the mass of amine curing agent required for every 100g of carboxyl graft-modified epoxy resin; M—molecular weight of amine curing agent; H n —The number of active hydrogen atoms on the amine group in the amine curing agent molecule; and E—Epoxy value of carboxyl grafted modified epoxy resin.
6. The base treatment agent according to any one of claims 1 to 4, characterized in that: The amine curing agent includes one or more of aliphatic amine, alicyclic amine, aromatic amine and polyamide; the active diluent is an epoxy or hydroxyl solvent; and the accelerator is a phenolic accelerator.
7. The base treatment agent according to claim 6, characterized in that: The accelerator includes one or more of phenol, 2,4,6-tris(dimethylaminomethyl)phenol, resorcinol, aminophenol, and halogenated phenol.
8. A method for preparing the base treatment agent according to any one of claims 1 to 7, characterized in that: The following steps are involved: mixing an amine curing agent, a reactive diluent, and an accelerator to obtain a mixture; The carboxyl graft-modified epoxy resin is mixed with the mixture to obtain the base layer treating agent.
9. A composite waterproof system, characterized in that: The invention comprises a base treatment layer, a non-asphalt non-curing waterproof coating layer, and an environmentally friendly waterproof coiled material which are stacked in sequence; wherein the base treatment layer is coated with the base treatment agent described in any one of claims 1 to 7.
10. The composite waterproof system according to claim 9, characterized in that: The environmentally friendly waterproofing membrane is a non-asphalt self-adhesive waterproofing membrane or a polymer waterproofing membrane.
Citation Information
Patent Citations
Waterborne epoxy modified acrylic resin and aqueous dispersion thereof
CN104513344A
Epoxy resin base layer treating agent matched with polyurethane waterproof coating and used for wet base layer, and preparation method of epoxy resin base layer treating agent
CN111171680A
Modified epoxy resin, preparation method of modified epoxy resin, emulsion preparation method of modified epoxy resin and application thereof
CN113004494A
An epoxy resin grouting material and its preparation method
CN114933782A
Non-asphalt-based non-curing waterproof coating and preparation method thereof
CN115418149A